PERJANJIAN KEMITRAAN PERTASHOP ANTARA PT. PERTAMINA PATRA NIAGA DAN MITRA USAHA DALAM PERLINDUNGAN KONSUMEN BAHAN BAKAR MINYAK - Deri Taraka; Sunaryo; Kasmawati; Sepriyadi Adhan; Ria Wierma Putri (The Juris, 2025)
This study aims to analyze the legal responsibilities of the parties in the partnership agreement between PT. Pertamina Patra Niaga and PT. Braja Slebah Energi (business partner) Pertashop. This study uses a normative legal method by reviewing laws and regulations, legal documents, and literature related to the substance of the Pertashop partnership agreement and fuel consumer protection. The results of the study indicate that PT Pertamina Patra Niaga plays a strategic role in the distribution and marketing of fuel throughout Indonesia through the Pertashop program as a partnership-based service innovation. The Pertashop partnership agreement is in the form of a standard written agreement prepared by PT. Pertamina Patra Niaga as the licensor and product owner with PT. Braja Slebah Energi as the operational manager of fuel distribution and sales. From the aspect of consumer protection, the implementation of fuel distribution through Pertashop has referred to Article 19 of the Consumer Protection Law which requires business actors to provide compensation for consumer losses. It can be concluded that the Pertashop program is an effective instrument in expanding the fuel distribution network in areas not yet served by gas stations through a partnership pattern. Although the cooperation agreement is standard and unilaterally drafted by Pertamina, it remains valid and binding on the parties, clearly defining roles and responsibilities. Furthermore, consumer protection in fuel distribution through Pertashop has a strong legal basis through the implementation of Article 19 of the Consumer Protection Law, which is outlined in the agreement, guaranteeing consumers' rights to compensation in the event of losses.